Conceptualizing energy security and the role of diversification as the key indicator against energy supply disruption - Tufail, Muhamad Mutasim Billah; Ibrahim, Jafni Azhan; Melan, Mustakim (Akademia Baru, 2018)
The importance of energy in modern civilization can never be denied. Developing and emerging economies of 21st century are facing dual challenge of Affordable and socially acceptable supplies of energy to its consumers. The security of energy supply and resources is one of the key objectives of global energy policies. However the concept of energy security, indicators and attributes are still unclear. The major focus of the wealthy countries of the world is to make the energy more clean and sustainable at any cost. However for developing and struggling nations the major object is to get the cheap and consisting supplies of energy for better development. This paper elaborates the terminology of energy security with respect to Availability, Accessibility, Affordability and acceptably and discuss the role of diversification in mitigation of security risk. It also highlights the indices of diversity measurement in energy system.